Modelling Characteristic of Respiration on Artificial Ripening System of Climacteric Fruit Based on Logistic Equation - Kem Trimaya Vanani; Sutrisno . (Jurnal Keteknikan Pertanian, 2002)
As perishable products, fruit have limited shelf life that could disturb the supply continuity on the market. A system consists of Cold storage and artificial ripening chamber could be a solution to this problem. Then, a mathematical model overcome the limited experiment time, expenses and technique.Over the past years, respiration models were built mostly by eksponential type of equations or air diffusion. This paper describes respiration models based on logistic growth model. The logistic model described a population growth in a sigmoid curve, which show slow increase at first, then sharpen until it slowed down to certain position influenced by inhibition factor. The accumulation of carbon dioxide of respiration in closed chamber showed the same symptoms. The inhibition factor used in the models is adapted from inhibition constant of Lee et al. (1992) respiration model, which based on enzyme kinetics. The model has successfully estimated climateric peak of Mas banana under three different length of cold storage, compared to secondary data.